2022
DOI: 10.1017/s1049096522001056
|View full text |Cite
|
Sign up to set email alerts
|

“No Better Way of Selecting the Man in Whom They Place the Highest Confidence”: A Note on James Madison’s Remarks on the Electoral College at Richmond’s Ratifying Convention

Abstract: This article discusses the remarks by James Madison to Virginia’s ratifying convention in June 1788 as they relate to the Electoral College. Madison’s remarks in Richmond shed light on his rarely highlighted expectations of the workings of the Electoral College and provide insight into the Constitutional Convention’s debate on the legislative selection of the President.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Herein, we certainly do not wish to enter this more normative debate about the merits of the Electoral College. It can indeed be observed that, at least for some of the framers of the Constitution, one goal of having an Electoral College arose from a distrust in the capacity of the public to keep their sangfroid in emotionally challenging times (Novotny, 2023). As Hamilton (1788) stated: “A small number of persons, selected by their fellow citizens from the general mass, will be most likely to possess the information and discernment requisite to so complicated an investigation.” It has to be noted that, from 1804, this assumption about the moderation exercised by the elite of the country no longer entered the debates (Kuroda, 1994).…”
mentioning
confidence: 99%
“…Herein, we certainly do not wish to enter this more normative debate about the merits of the Electoral College. It can indeed be observed that, at least for some of the framers of the Constitution, one goal of having an Electoral College arose from a distrust in the capacity of the public to keep their sangfroid in emotionally challenging times (Novotny, 2023). As Hamilton (1788) stated: “A small number of persons, selected by their fellow citizens from the general mass, will be most likely to possess the information and discernment requisite to so complicated an investigation.” It has to be noted that, from 1804, this assumption about the moderation exercised by the elite of the country no longer entered the debates (Kuroda, 1994).…”
mentioning
confidence: 99%